ANALISIS YURIDIS TERHADAP PENERIMA HIBAH YANG MELEBIHI KETENTUAN DALAM FIQIH DAN KOMPILASI HUKUM ISLAM (Studi Kasus Putusan Pengadilan Agama Medan Nomor 616/Pdt.G/2010/PA-Mdn) - INDAMAYASARI INDAMAYASARI (PREMISE LAW JURNAL, 2016)
Hibah is giving an object to another person who is still alive voluntarily without expecting any reward. KHI gives the limitation of hibah for only 1/3 of the property. The legal consequence of hibah which exceeds the provision in the Islamic fiqh and in KHI is considered illegal and can be cancelled by the Religious Court if any of the other heirs file a complaint. Judge’s consideration on the cancellation of hibah No. 616/Pdt.G/2010/PA-Mdn is first, hadist of the Prophet Muhammad, ”parents can get back what is given [to their children].” Secondly, hibah which is more than 1/3 of the property is illegal. Thirdly, the receiver of hibah breaches the agreement given by his parents. Fourthly, the receiver of hibah cannot prove the sales agreement, except only hibah certificate. Fifthly, the receiver of hibah states that the debenture he owns is based on the sales agreement. Keywords: Hibah that Exceeds Provision, Fiqh, Compilation of the Islamic Law